Numerical Investigation of Birefringene Effect on the Light Reflection - Masoud Rezvani Jalal; Farzad Vaziri Alamdarlo (Journal of Optoelectronical Nanostructures, 2016)
In the present paper, the problem of light reflection from a birefringent medium and thin film is considered. First, the analytical equations governing the propagation of a plane and harmonic electromagnetic wave in an infinite, birefringent, linear, non-dispersive, non-absorbing, and non-magnetic medium is derived from Maxwell equations. Then, using phase matching condition and boundary conditions, the governing equations of reflection and transmission from a birefringent medium is obtained. Next, the reflection of s and p polarizations in incidence of s-polarized, p-polarized, and circularly polarized light on a plane surface is calculated using a massive computer code developed by the authors. Calculations show that the polarizations are mixed and converted to each other. On the other hand, dependence of reflection on azimuthal incidence angle is revealed. Then, the problem of interfering reflection from a birefringent thin film is regarded. The computer code calculates reflection of light from the film by considering the successive reflections and transmissions from the upper and lower surfaces of the film through two-reflection approach. Calculations show that, in reflection of white light from the film, a kind of banding is developed which is absent in isotropic films. Observation of reflection increase by increasing birefringent properties is another finding of the paper.